2023 Chinese guideline for lipid management - Li, Jian-Jun; Zhao, Shui-Ping; Zhao, Dong; Lu, Guo-Ping; Peng, Dao-Quan; Liu, Jing; Chen, Zhen-Yue; Guo, Yuan-Lin; Wu, Na-Qiong; Yan, Sheng-Kai; Wang, Zeng-Wu; Gao, Run-Lin; et al. (Frontiers in Pharmacology, 2023)
Atherosclerotic cardiovascular disease (ASCVD) is the leading cause of death among urban and rural residents in China, and elevated low-density lipoprotein cholesterol (LDL-C) is a risk factor for ASCVD. Considering the increasing burden of ASCVD, lipid management is of the utmost importance. In recent years, research on blood lipids has made breakthroughs around the world, hence a revision of China guidelines for lipid management is imperative, especially since the target lipid levels in the general population vary in respect to the risk of ASCVD. The level of LDL-C, which can be regarded as appropriate in a population without frisk factors, can be considered abnormal in people at high risk of developing ASCVD. As a result, the "Guidelines for the prevention and treatment of dyslipidemia" were adapted into the "China Guidelines for Lipid This is a provisional file, not the final typeset articleManagement" (henceforth referred to as the new guidelines) by an Experts' committee after careful deliberation. The new guidelines still recommend LDL-C as the primary target for lipid control, with cardiovascular disease (CVD) risk stratification to determine its target value. These guidelines recommend that moderate intensity statin therapy in adjunct with a heart-healthy lifestyle, be used as an initial line of treatment, followed by cholesterol absorption inhibitors or/and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors, as necessary. The new guidelines provide guidance for lipid management across various age groups, from children to the elderly. The aim of these guidelines is to comprehensively improve the management of lipids and promote the prevention and treatment of ASCVD by guiding clinical practice.